2017
DOI: 10.2298/tsci17s1217w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the drag coefficient of supercritical water flow past sphere-particle at low reynolds numbers

Abstract: Supercritical water fluidized bed is novel reactor for the efficient gasification of coal to produce hydrogen. The Euler-Euler and Euler-Lagrange methods can be used to simulate the flow behaviors supercritical water fluidized bed. The accuracy of the simulated results with the two methods has a great dependence on the drag coefficient model, and there is little work focused on the study on particle's drag force in supercritical water. In this work, the drag coefficients of supercritical water flow past a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The flow is stable and symmetric within the range of Re less than 210 . Previous studies have shown that the flow of SCW around particles at Re ≤ 200 is a stable symmetrical flow. The Re range of this work is 25–200. The physical properties of SCW vary with temperature, which causes the drag force of interactive particles to change.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…The flow is stable and symmetric within the range of Re less than 210 . Previous studies have shown that the flow of SCW around particles at Re ≤ 200 is a stable symmetrical flow. The Re range of this work is 25–200. The physical properties of SCW vary with temperature, which causes the drag force of interactive particles to change.…”
Section: Methodsmentioning
confidence: 77%
“…Regardless of gravity and radiation heat transfer, the governing equation can be written as follows: where ρ is the density, u is the velocity, μ is the dynamic viscosity, p is the pressure, H is the enthalpy, K is the kinetic energy, λ is the thermal conductivity, T is the temperature. Previous work has shown that algorithms and discrete formats do not require special processing for SCW. The numerical method used in this work is direct numerical simulation (DNS). Therefore, the algorithm for solving the N-S equation uses SIMPLE, where the discrete format of convection terms uses second-order upwind.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to differing microsphere diameters, this transition occurs at lower Re values for the D p = 3.7 µm, P = 760 Torr case than the D p = 7.6 µm, P = 760 Torr case. As the microsphere's velocity continues to decrease below M = 0.8, the flow separation point moves to the downstream side of the microsphere and the low-pressure zone in the microsphere's wake reduces in volume [22,23,25,26]. While the reduction of the low-pressure region induces a decrease in pressure drag, the concurrent increase in friction drags results in a monotonic net increase in C D .…”
Section: Resultsmentioning
confidence: 99%
“…For detailed information on the interaction between the particles and fluid, particle-resolved direct numerical simulation (PR-DNS) becomes a powerful and valuable tool for studying the internal SCW–solid particle flow behavior. , Wei et al established a numerical model that fully accounts for variation in thermophysical properties in the pseudo-critical zone of SCW and showed the critical effect of the variable thermophysical properties of SCW on the flow separation and mixed , and free convection by the PR-DNS. Wu et al , expanded the work on a cylinder and sphere particle in SCW and examined the effect of the particle shape on the drag force. PR-DNS on the drag and heat transfer process of a single rough surface particle and double particles in SCW was investigated by Jin et al , Zhang et al discussed the effect of the spheroid aspect ratio on sphere Cd and Nu that combined the influence of the thermophysical properties of SCW in different temperature and pressure ranges; then, they considered the effect of the incident angle of the spheroid and improved the correlations of Cd and Nu in SCW.…”
Section: Introductionmentioning
confidence: 99%